Análise Citogenética em Lagria villosa (COLEOPTERA, TENEBRIONIDAE): enfase na evolução cromossômica - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
TheColeopterahave a large variationof the sex determinationsystem, being the Xypmechanism considered ancestorfor thisorder. The presenceof a argyrophilous material associated with thesexbivalent is described asresponsible formaintenance andassociation of thesechromosomes.However,there is no consensus in the literature about the nature ofthisargyrophilous material. In addition,few species have been studied using fluorescence in situhybridization (FISH) tothe location of the multigene families, which areuseful and can elucidate the variation in the karyotype and genomic organization of several species.To date,there is no cytogenetic analysis in the genus Lagria.Thus, theaim of this study was tocharacterizecytogeneticallyLagriavillosa, throughconventional andmolecularcytogenetics, forinvestigating the mechanism ofassociationofsex chromosomesXyp,through analysis of nature of argyrophilous material in the lumen of sex bivalent. Additionally, thechromosomalmapping of 5S rDNA multigene families, 18S rDNA and histone H3 genes in L. villosa, was carried out, and showing for the first timein Coleoptera, that genes 18S and 5S DNAs are interspersed. In addition, the analysis oftesticular cellsshowed 2n=18=16+Xypand formulameiotic 2n=8II+Xyp.In this workwe discuss thepossible mechanismsevolvingin the association ofXypsex chromosomes,where it is consideredthat the combination ofsynaptonemalcomplex proteinsmayparticipate in thecorrect segregationofchromosomes.In addition, the fiber-FISH technique with dual probes (18S and 5S) was used for better resolution mapping of these regions in L. villosa, showing that the two DNAs are closely interspersed with varying amounts of both classes of DNA. Association between the two rDNA families have been reported for other species and different hypotheses are raised about the functional organization in these families.
Keywords: heterocromatina; DNAr; região organizadora de nucléolo; sistema de determinação sexual; famílias multigênicas; histonas; heterochromatin; rDNA; nucleolarOrganizerRegion; Sex DeterminationSystem; histone; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR